Training Program for Sense of Ownership Harmonization - Hubeladze, Iryna (Psychological Prospects Journal, 2021)
Purpose. The purpose of the article is to develop the content and structure and presentation as well of the author’s training program to harmonize the sense of ownership of the person. Methods. A number of methods for interactive work and psychoeducation were used to develop the training program in order to the sense of ownership harmonize: the method of incomplete sentences, role play, simulation, brainstorming, group work, discussion, psychological workshops, creative homework and more. Results. The article presents the author’s training program to harmonize the sense of ownership, which consists of an introduction, final part and three main modules: "Sense of ownership as a socio-psychological phenomenon: mine, ours, someone else’s, nobody’s", "Factors of strengthening the sense of ownership: control, self-investment and intimate knowledge"," Consequences and opportunities for sense of ownership harmonization". Each of the modules aims to develop different components of a sense of ownership: control, self-investment of money, time or other resources and deep intimate knowledge. The total amount of the training program is 26 academic hours. The proposed training program can be used to harmonize the sense of ownership, both among high school and university students, and among the adult population in general. Conclusions. The introduction and study of the effectiveness of the training program to harmonize the sense of ownership showed the feasibility of its use among high school and student youth, as well as adults, which helped to optimize responsibility, self-efficacy, self-identity and involvement. The prospects for further research are in the development of a psychological training program to harmonize the sense of ownership of the local community and own country.